(untitled) (Tamalanrea: Journal of Government and Development (JGD), 2025)
The implementation of the 2020 Makassar Mayoral Election shows that the level of political participation is still low. This condition needs to be evaluated by reviewing the extent of the role of various parties in encouraging increased community political participation. Political education is the main key in building public political awareness. The Indonesian Youth National Committee (KNPI) of Makassar City has a role in increasing voter participation through political education. The purpose of this research is to find out the political education of the National Committee of Indonesian Youth (KNPI) Makassar City in increasing voter participation. This research method uses a descriptive qualitative approach, with data collection techniques through in-depth interviews, field observations, documentation, literature studies and online media. The results showed that the Makassar City KNPI has a role in increasing public political awareness, especially among young voters, through neutral and independent political education. This is realized through cooperation with the KPU and Bawaslu, board development, and physical and digital socialization efforts. However, effectiveness still faces various challenges, such as political apathy, distrust of the system, lack of method development, lack of youth representation in local politics, and the stigma of organizational independence. Therefore, there is a need for greater collaboration and innovative approaches to overcome barriers to youth political participation more effectively.